Atomic layer deposition on 2D transition metal chalcogenides: Layer dependent reactivity and seeding with organic ad-layers - Wirtz, Christian; Hallam, Toby; Cullen, Conor Patrick; Berner, Nina C.; O'Brien, Maria; Marcia, Mario; Hirsch, Andreas; Duesberg, Georg S. (Chemical Communications, 2015)
This commmunication presents a study of atomic layer deposition of Al2O3 on transition metal dichalcogenide (TMD) two-dimensional films which is crucial for use of these promising materials for electronic applications. Deposition of Al2O3 on pristine chemical vapour deposited MoS2 and WS2 crystals is demonstrated. This deposition is dependent on the number of TMD layers as there is no deposition on pristine monolayers. In addition, we show that it is possible to reliably seed the deposition, even on the monolayer, using non-covalent functionalisation with perylene derivatives as anchor unit.

Highly Integrated Organic–Inorganic Hybrid Architectures by Noncovalent Exfoliation of Graphite and Assembly with Zinc Oxide Nanoparticles - Marcia, Mario; Vinh, Chau; Dolle, Christian; Abellan Saez, Gonzalo; Schönamsgruber, Jörg; Schunk, Torsten; Butz, Benjamin; Spiecker, Erdmann; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2016)
Liquid-phase exfoliated few-layer graphene flakes are noncovalently functionalized with tailor-made cationic water-soluble perylene diimides. By using a straightforward dip-coating approach, homogeneous ultrathin films consisting of interpenetrated nanoarchitectures can be achieved by incorporation of anionic ZnO nanoparticles. These 0D/2D assemblies pave the way for the development of novel graphene-based composite materials.
Keywords: graphene; hybrid materials; layer-by-layer assembly; nanoparticles; supramolecular chemistry

Noncovalent Functionalization of Black Phosphorus - Abellan Saez, Gonzalo; Lloret Segura, Vicente Josep; Mundloch, Udo; Marcia, Mario; Neiß, Christian; Görling, Andreas; Varela, Maria; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie-International Edition, 2016)
Black phosphorus (BP) was functionalized with organic moieties on the basis of liquid exfoliation. The treatment of BP with electron-withdrawing 7,7,8,8-tetracyano-p-quinodimethane (TCNQ) led to electron transfer from BP to the organic dopant. On the other hand, the noncovalent interaction of BP with a perylene diimide was mainly due to van der Waals interactions but also led to considerable stabilization of the BP flakes against oxygen degradation.
Keywords: Black phosphorus; Charge transfer; Functionalization; Noncovalent interactions; Stability

Novel EDTA-ligands containing an integral perylene bisimide (PBI) core as an optical reporter unit - Marcia, Mario; Singh, Prabhpreet; Hauke, Frank; Maggini, Michele; Hirsch, Andreas (Organic & Biomolecular Chemistry, 2014)
The synthesis, characterization and metal complexation of a new class of perylene bisimides (PBIs) as an integral part of ethylenediaminetetraacetic acid (EDTA) are reported. The simplest representative, namely derivative 1a, was synthesized both by a convergent as well as a direct approach while the elongated derivatives, 1b and 1c, were obtained only via a convergent synthetic pathway. All these new prototypes of water-soluble perylenes are bolaamphiphiles and were fully characterized by H-1- and C-13-NMR spectroscopy, matrix assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry and IR spectroscopy. In order to acquaint ourselves with the behaviour in solution of our PBIs bearing dendritic wedges, the simplest derivative, 1a, was chosen and tested by means of UV/Vis and fluorescence spectroscopy as well as by zeta-potential measurements. A photoexcitation induced intramolecular photo-electron transfer (PET) can be observed in these molecules. Therefore their potential applications as sensors can be imagined. Model compound 1a efficiently coordinates trivalent metal cations both in water and dimethyl sulfoxide (DMSO). Significantly, the effects of the complexation strongly depend on the aggregation state of the PBI molecules in solution. As a matter of fact, in water, the presence of M3+ ions triggers the formation of light emitting supramolecular aggregates (excimers). On the other hand, in DMSO-rich solutions metal complexation leads to the suppression of the PET and leads to a strong fluorescence enhancement.

Optimized single-layer MoS2 field-effect transistors by non-covalent functionalisation - Kim, HyunJeong; Kim, WungYeon; O'Brien, Maria; Mcevoy, Niall; Yim, Chanyoung; Marcia, Mario; Hauke, Frank; Hirsch, Andreas; Kim, Gyu-Tae; Duesberg, Georg (Nanoscale, 2018)
Field-effect transistors (FETs) with non-covalently functionalised molybdenum disulfide (MoS2) channels grown by chemical vapour deposition (CVD) on SiO2 are reported. The dangling-bond-free surface of MoS2 was functionalised with a perylene bisimide derivative to allow for the deposition of Al2O3 dielectric. This allowed the fabrication of top-gated, fully encapsulated MoS2 FETs. Furthermore, by the definition of vertical contacts on MoS2, devices, in which the channel area was never exposed to polymers, were fabricated. The MoS2 FETs showed some of the highest mobilities for transistors fabricated on SiO2 with Al2O3 as the top-gate dielectric reported so far. Thus, gate-stack engineering using innovative chemistry is a promising approach for the fabrication of reliable electronic devices based on 2D materials.

Perylene-based non-covalent functionalization of 2D materials - Marcia, Mario; Hauke, Frank; Hirsch, Andreas (FlatChem, 2017)
Keywords: 2D materials; Black phosphorus; Boron nitride; Graphene; Non-covalent functionalization; Perylene; Transition metal dichalcogenides